Keunggulan Bersaing di Era Digital: Analisis Strategi PT Telkom Indonesia - Warnila, Warnila; Oktaviyah, Nurafni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
To build competitive advantage, companies must carry out the role of strategic management and understand the strategies being implemented. The purpose of this writing is to comprehensively describe and analyze the specific strategies implemented by PT Telkom Indonesia in facing competition in the digital telecommunications industry. This research will explore various strategic initiatives carried out by the company. This research uses a descriptive qualitative approach to analyze PT Telkom Indonesia's competitive strategy in the digital era. In this research, we used secondary data sources that came from literature books and previous research journals related to the research topic discussed. From the results and discussion of the research above, conclusions are drawn which show that in the ever-growing digital era, PT Telkom Indonesia has succeeded in implementing key strategies to maintain competitive advantage in the telecommunications market. Through investments in digital infrastructure, product and service innovation, digital talent development, improved customer experience, and strategic partnerships, Telkom Indonesia has strengthened its position as a market leader.Tujuan penulisan ini adalah untuk mendeskripsikan dan menganalisis secara komprehensif strategi khusus yang diterapkan PT Telkom Indonesia dalam menghadapi persaingan di industri telekomunikasi digital. Penelitian ini akan mengeksplorasi berbagai inisiatif strategis yang dilakukan perusahaan. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk menganalisis strategi bersaing PT Telkom Indonesia di era digital. Dalam penelitian ini kami menggunakan sumber data sekunder yang bersumber dari buku literatur dan jurnal penelitian terdahulu yang berkaitan dengan topik penelitian yang dibahas. Dari hasil dan pembahasan penelitian di atas, diambil kesimpulan yang menunjukkan bahwa di era digital yang semakin berkembang, PT Telkom Indonesia berhasil menerapkan strategi-strategi utama untuk mempertahankan keunggulan kompetitif di pasar telekomunikasi. Melalui investasi pada infrastruktur digital, inovasi produk dan layanan, pengembangan talenta digital, peningkatan pengalaman pelanggan, dan kemitraan strategis, Telkom Indonesia telah memperkuat posisinya sebagai pemimpin pasar.